Coordination with Differential Time Preferences: Experimental Evidence - Marina Agranov; Jeongbin Kim; Leeat Yariv (Center for Economic Studies and ifo Institute (CESifo), 2023)
The experimental literature on repeated games has largely focused on settings where players discount the future identically. In applications, however, interactions often occur between players whose time preferences differ. We study experimentally the effects of discounting differentials in infinitely repeated coordination games. In our data, differential discount factors play two roles. First, they provide a coordination anchor: more impatient players get higher payoffs first. Introducing even small discounting differentials reduces coordination failures significantly. Second, with pronounced discounting differentials, intertemporal trades are prevalent: impatient players get higher payoffs for an initial phase and patient players get higher payoffs in perpetuity afterward.
Keywords: C73; C92; D15; D25; 330; repeated games; discounting; intertemporal trade; experiments